The Influence of the Problem-Based Learning Model on Students' Comprehension of the Concept of Pressure in Solids in Grade IX - Jeanny Octaviany; Rahayu Kariadiinata; Muhammad Minan Chusni (International Journal of Science, Technology and Applications, 2025)
The learning model used in learning science concepts should have a strong influence or impact on students'  understanding of a science concept. Researchers in this case conducted research related to the Influence of  the Problem Based Learning Learning Model carried out at SMPN 2 Solokanjeruk with samples of class  IX-I on the concept of Pressure on Solids .Researchers conducted a pretest test before conducting learning  with the Problem Based Learning learning model, and conducted a posttest test after conducting learning  using the Problem Based Learning Learning Model. After conducting inferential statistical analysis (2  related samples), Researchers found that Science Learning with the Problem Based Learning Learning  model had a strong impact on student learning outcomes. The results of the N-Gain data analysis had an  average score of 59.9817 or 0.599817, namely, the increase in students' science understanding was in the  moderate category, with an N-Gain percentage of 59.9817% having a fairly effective category. The results  of this research study identified an increase in high science understanding of 41%, an increase in medium  science understanding of 49%, an increase in low science understanding of 5%, no increase in  understanding of 2.5%, and a decrease in understanding of 2.5%. Based on this, the Problem based learning  model on the concept of Pressure on Solids for class IX-I students of SMPN 2 Solokanjeruk has a fairly  good impact on students' science understanding.